Postprandial Hypotension in Elderly Patients: Pathophysiology, Diagnosis and Prevention Measures - O. N. Antropova; A. A. Efremushkina (Архивъ внутренней медицины)
Postprandial hypotension (PPH) is an important but underrecognized condition resulting from an inadequate compensatory cardiovascular response to meal-induced visceral blood pooling. PPG is recognized as an important clinical problem because it has a high prevalence in the older age group and is associated with the development of cardiovascular complications and geriatric syndromes. Possible pathophysiological mechanisms of PPG: increased visceral blood flow; weakening of baroreflex function due to disorders associated with age or autonomic dysfunction; inappropriate activation of sympathetic nerves; dysregulation of vasoactive intestinal peptides; insulin-mediated vasodilation. Ask about symptoms of postprandial hypotension and a decrease in systolic blood pressure (BP) of ≥20 mm Hg. Art. 15-60 minutes after eating is of paramount importance for making a diagnosis of PPG. One of the main strategies for preventing PPG is to reduce gastric distension (small meals and more frequent meals), resting on your back after eating, and drinking enough water. Walking after eating also appears to help restore blood pressure after eating. Caution should be exercised when prescribing protein supplements in the elderly, modifying the diet by replacing high-nutrient sweeteners with low-calorie sweeteners (d-xylose, xylitol, erythritol, maltose, maltodextrin, and tagatose). Metformin or acarbose modulates the cardiovascular response in patients with diabetes mellitus and reduces postprandial hypotension. Thus, PPG is a fairly common and clinically significant phenomenon in elderly patients. Increasing the awareness of doctors about pathophysiology and methods of diagnosis and prevention will improve the efficiency and safety of managing geriatric patients.